2022
DOI: 10.3390/biom12111620
|View full text |Cite
|
Sign up to set email alerts
|

Tears as a Source of Biomarkers in the Diagnosis of Graves’ Orbitopathy

Abstract: Thyroid eye disease (TED) is a poorly understood autoimmune manifestation of thyroid diseases most commonly associated with Graves’ disease. Due to a lack of specific biomarkers and uncertain signs and symptoms, Graves’ orbitopathy (GO) is challenging to diagnose early and treat effectively. Nowadays, there is great interest in searching for precise molecular biomarkers for early detection, disease monitoring, and clinical management. Researchers are keen to identify novel methods to predict and diagnose disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Elevelevated oxidative stress may lead to impaired lacrimal glands and induce the accumulation of carbon-sylated proteins in the lacrimal glands ( 71 ), thus leading to multifocal inflammation and fibrosis around the lacrimal acinar cells. Furthermore, studies indicated altered regulatory effects of pro-inflammatory and protective proteins in tears of Sjogren’s syndrome ( 72 , 73 ) and thyroid-associated orbitopathy ( 74 , 75 ), reflecting both autoimmune and inflammation-induced lacrimal gland dysfunction. Studies have pointed out that eye diseases can also participate in inflammation-related pathways to cause lacrimal gland function changes ( 76 ).…”
Section: Discussion and Insightmentioning
confidence: 99%
“…Elevelevated oxidative stress may lead to impaired lacrimal glands and induce the accumulation of carbon-sylated proteins in the lacrimal glands ( 71 ), thus leading to multifocal inflammation and fibrosis around the lacrimal acinar cells. Furthermore, studies indicated altered regulatory effects of pro-inflammatory and protective proteins in tears of Sjogren’s syndrome ( 72 , 73 ) and thyroid-associated orbitopathy ( 74 , 75 ), reflecting both autoimmune and inflammation-induced lacrimal gland dysfunction. Studies have pointed out that eye diseases can also participate in inflammation-related pathways to cause lacrimal gland function changes ( 76 ).…”
Section: Discussion and Insightmentioning
confidence: 99%
“…Cai et al, found that patients with inactive TED had higher levels of IL-7 when compared to healthy controls and active TED patients, respectively [147]. Tear levels of IL-15 and IL-17 have also been found to be increased in active TED compared to inactive TED [148]. Huang et al, not only confirmed the previous findings but also found positive correlations between levels of IL-1β, IL-6, and IL-17A and clinical activity score, which points to a potential future use in assessing disease's severity [149].…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…sis factor alpha (TNF-a), and IL-2, and IL-17A, have been demonstrated in tears compared to controls [10]. Because of the many similarities observed between the symptoms of DED and the initial symptoms of TO with respect to the cytokine and protein markers presented, differentiating them is essential.…”
Section: Reviewmentioning
confidence: 99%
“…The concentration of lysozyme C was significantly higher in TO compared to DED. Thus, the tear proteome test showed a different panel of proteins in patients with TO and those with DED, which is potentially useful for screening and differential diagnosis [10,11].…”
Section: Reviewmentioning
confidence: 99%